Net-metering and net-billing in photovoltaic self-consumption: The cases of Ecuador and Spain. (October 2022) - Ordóñez, Ángel; Sánchez, Esteban; Rozas, Lydia; García, Raúl; Parra-Domínguez, Javier
Graphical abstract: Highlights: Comparative Analysis of self-consumption in residential sector. Feasibility of self-consumption conditioned by country-specific scenarios. Profitable in Spain for consumptions above 2, 000 kWh/year. Not profitable in Ecuador for the average consumer and only above 6, 000 kWh/year. Net-billing promotes smarter photovoltaic installations. Abstract: Solar Photovoltaics has become one of the cheapest sources of electricity, with the potential to expand further through distributed generation. PV self-consumption can empower electricity customers, transforming them into prosumers, but its success relies on appropriate regulations, especially in the treatment of surplus electricity, being net-metering and net-billing the most common remuneration mechanisms. As the number of such PV systems increases, regulation needs to evolve and may affect profitability. The purpose of this research is to take advantage of the Spanish experience, establishing key points that can improve the regulation in Ecuador and other countries. The operation of these remuneration schemes is studied through an economic analysis for a wide range of residential customers, highlighting the low profitability of small PV installations, which are not profitable for the average consumer in Ecuador. Grid parity is reached in Spain over 3 kW and in Ecuador only for the highest electricity consumers. Although the net-billing model is more effective in promoting PV self-consumption in the medium and long term, it requires additional conditions, such as those in Spain. Some recommendations are proposed, e.g. additional support with progressive tax reductions, simplication of permits and the introduction of collective self-consumption.